Postoperative Aspirin Use and Its Effect on Bone Healing in the Treatment of Ankle Fractures. Issue 4 (16th October 2019) - Hunter, Allison; Pitts, Charles; Montgomery, Tyler; Anderson, Matthew; Wilson, John T.; Buddemeyer, Katherine; McGwin, Gerald; Johnson, Michael
Category: Ankle, Trauma Introduction/Purpose: There is hesitancy to administer nonsteroidal anti-inflammatories (NSAIDs) within the postoperative period following fracture care due to concern for delayed union or nonunion. However, aspirin (ASA) is routinely used for chemoprophylaxis of deep vein thrombosis (DVT) and is gaining popularity for use after treatment of ankle fractures. We examine the incidence of nonunion of operative ankle fractures and risk of DVT in patients who did and did not receive postoperative ASA. We hypothesize that time to clinical and radiographic union and the risk of DVT are no different. Methods: A retrospective chart review was performed on all patients treated between 2008 and 2018 for ankle fractures requiring operative fixation by three Foot and Ankle fellowship trained orthopaedic surgeons at a single institution with a minimum of 3 months follow up. Demographics, preoperative comorbidities, and postoperative medical and surgical complications were compared between patients who did and did not receive ASA postoperatively. For both groups, union was evaluated by clinical exam as well as by radiograph. Results: 506 patients met inclusion criteria: 152 received ASA and 354 did not. Radiographic healing at 6 weeks was demonstrated in 95.9% (94/98) and 98.6% (207/210) respectively (p-value .2134). There was no significant difference in time to radiographic union between groups. The risk of postoperative DVTs in those with and without ASA was not significantly different (0.7% (1/137) vs 1.2% (4/323), respectively; p-value .6305). Conclusion: Postoperative use of ASA does not delay radiographic union of operative ankle fractures or affect the rate of postoperative DVT. This is the first and largest study to examine the effect of ASA on time to union of ankle fractures.